A erosão costeira e sua influência sobre a atividade petrolífera: alternativas sustentáveis na mitigação de impactos ambientais - Nascimento, Miriam Cunha do (2009)
The study area consist in high sensitivity environments located on the northern coast of Rio Grande do Norte, Northeast Brazil. The barrier island are the main geomorphological features on the coastal landscape, being naturally instable and surrounded by industrial activities like oil fields, salt industry, shrimp farms and urban areas sometimes installed parallel to the coast, combined with coast engineering interventions. High energy hydrodynamic process are responsible for the morphological instability of the coast. The study was based on remote sensing data obtained between 1954 and 2007 which consist in orbital images from Landsat, CBERS and Ikonos satellites and aerial photos. With all data integrated on GIS environment it was possible to update thematic maps of geology, geomorphology, vegetation, soil and landuse and development of multitemporal maps pointing areas with erosion and depositions of sediments, defining the critical erosion process on this region. The bigger morphological changes are related to changes on wind patterns during the year, terrestrial and sea breezes during the day, with spits and barrier island migration, opening and closing of channels like the one parallel to the coast on the area of Serra and Macau oil fields. These factors combined with the significant reduction on sediment budgets due to the loss of natural spaces to sediment reworking contribute to the low resilience which tends to be growing on the area of Serra and Macau oil fields. In front of such scenery a detailed monitoring was done in order to find technological possibilities for coastal restoration. A pilot area was defined to start the project of mangrove restore together with beach nourishment in order to minimize the effect of the erosion caused by the channel parallel to the coast, contributing to stabilize the northeast channel as the main one. It s expected that such methodology will aid the coastal environments restoration and the balance between industrial activities and coastal erosion